TBX3 Knockdown Decreases Reprogramming Efficiency of Human Cells - Moritz Klingenstein; Stefanie Raab; Kevin Achberger; Alexander Kleger; Stefan Liebau; Leonhard Linta (Hindawi Limited, 2016)
TBX3 is a member of the T-box transcription factor family and is involved in the core pluripotency network. Despite this role in the pluripotency network, its contribution to the reprogramming process during the generation of human induced pluripotent stem cells remains elusive. In this respect, we performed reprogramming experiments applying TBX3 knockdown in human fibroblasts and keratinocytes. Knockdown of TBX3 in both somatic cell types decreased the reprogramming efficiencies in comparison to control cells but with unchanged reprogramming kinetics. The resulting iPSCs were indistinguishable from control cells and displayed a normal in vitro differentiation capacity by generating cells of all three germ layers comparable to the controls.